2018
DOI: 10.1177/1081286518774090
|View full text |Cite
|
Sign up to set email alerts
|

Indentation load–depth relation for an elastic layer with surface tension

Abstract: Load-depth relation is the fundamental requisite in nanoindentation tests for thin layers, however, the effects of surface tension are seldom included. This paper concerns micro-/nano-sized indentation of a bonded elastic layer by a rigid sphere. The surface Green's function with the incorporation of surface tension is first derived by applying the Hankel integral transform, and subsequently used to formulate the governing integral equation for the axisymmetric contact problem. By using a numerical method base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Several theoretical and experimental results have demonstrated the essential roles of size effect and surface effect on contact behavior when the indentation depth or punch size of materials are at the micro-/nano-scale [12][13][14]. In particular, due to the increasing ratio of the surface to bulk volume of materials at the nano-scale, the surface effect on nanocontact behavior played a dominant role [15,16]. Gurtin and Murdoch [17] first built surface elasticity theory to describe the surface effect of elastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and experimental results have demonstrated the essential roles of size effect and surface effect on contact behavior when the indentation depth or punch size of materials are at the micro-/nano-scale [12][13][14]. In particular, due to the increasing ratio of the surface to bulk volume of materials at the nano-scale, the surface effect on nanocontact behavior played a dominant role [15,16]. Gurtin and Murdoch [17] first built surface elasticity theory to describe the surface effect of elastic materials.…”
Section: Introductionmentioning
confidence: 99%
“…For nanoindentation with the indentation depth on the order of nanometers, the surface mechanics should be required to analyze the indentation test. Owing to the large specific surface area of materials at micro-/ nano-scale, the surface dependence of materials has been well recognized in recent years (Dingreville et al, 2005;Li et al, 2019;Wong et al, 1997). In particular, both atomistic simulations and experiments strongly revealed that surface effect played an essential role in contact problems for the indentation depths less than 100 nanometers (Mohammadi and Sharma, 2012;Wang and Feng, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2019a) investigated the contact between a conical asperity and a rough surface possessing surface tension. Based on parametric studies, Li et al (2019b) developed empirical expressions of indentation load-depth and load-contact radius relations for an elastic layer with surface tension.…”
mentioning
confidence: 99%